BIOSTRATIGRAPHY OF JURASSIC-CRETACEOUS BOUNDARY SEDIMENTS IN THE EASTERN CRIMEA - Arkad'ev V.V.; Savel'eva Yu.N.; Fedorova A.A.; Tesakova E.M. (My University, 2006)
The Dvuyakornaya Formation section in the eastern Crimea is described and subdivided into biostratigraphic units based on ammonites, foraminifers, and ostracodes. The lower part of the formation contains first discovered ammonites of the upper Kimmeridgian (Lingulaticears cf. procurvum (Ziegler), Pseudowaagenia gemmellariana Olóriz, Euvirgalithacoceras cf. tantalus (Herbich), Subplanites sp.) and Tithonian (?(Lingulaticeras efimovi (Rogov), Phylloceras consaguineum Gemmellaro, Oloriziceras cf. schneidi Tavera, and Paraulacosphinctes cf. transitorius (Oppel)). Based on the assemblage of characteristic ammonite species, the upper part of the formation is attributed to the Berriasian Jacobi Zone. Five biostratigraphic units (zones and beds with fauna) distinguished based on foraminifers are the Epistomina ventriosa-Melathrokerion eospirialis Beds and Anchispirocyclina lusitanica-Melathrokerion spirialis Zone in the upper Kimmeridgian-Tithonian, the Protopeneroplis ultragranulatus-Siphoninella antiqua, Frondicularia cuspidiata-Saracenaria inflanta zones, and Textularia crimica Beds in the Berriasian. The Cyrherelloidea tortuosa-Palaeocytheridea grossi Beds of the Upper Jurassic and Raymoorea peculiaris-Eucytherura ardescae-Protocythere revil Beds of the Berriasian are defined based on ostracodes. A new biostratigraphic scale is proposed for the upper Kimmeridgian-Berriasian of the eastern Crimea. The Dvyyakornaya Formation sediments are considered as deepwater facies accumulated on the continental slope. © MAIK "Nauka/Interperiodica" 2006.
Keywords: AMMONITES; BERRIASIAN; BIOSTRATIGRAPHY; CORRELATION; EASTERN CRIMEA; FORAMINIFERS; OSTRACODES; TITHONIAN; UPPER KIMMERIDGIAN; Мезозой::Меловая::Нижний::Берриасский; Мезозой::Юрская::Верхний::Киммериджский; Мезозой::Юрская::Верхний::Титонский; Mesozoic::Cretaceous::Lower::Berriasian; Mesozoic::Jurassic::Upper::Kimmeridgian; Mesozoic::Jurassic::Upper::Tithonian